EFFECT OF REWARD EXTRINSIC AND PERSON JOB FIT ON PERFORMANCE EMPLOYEES (STUDY ON MINING COMPANY) - Lorensa, Devia; Asriani, Asriani; Andrianto, Tedy (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2020)
This study aims to analyze the effect of extrinsic rewards and person job fit on the performance of mining company employees. The population that is used in research this is of entire departments that exist in the Company mines with the number of samples as much as 10 0 people. Research carried out by using the approach quantitative. Data of the respondents is processed using a technique analysis of regression linear multiple. Based on data collected using the study of literature, interviews, and questionnaires show that reward extrinsic not affect significantly on the performance of employees at the company's mine for the reward Intrinsic may need to consider their reward instrinsik the form of non- financial. While person job fit has a significant effect because the company has implemented the system, one of which is to improve performance and reduce employee turnover intention.